Resistant patterns of bacteria isolated from bloodstream infections at a university hospital in Delhi - M S Alam; P K Pillai; Prem Kapur; K K Pillai (Wolters Kluwer Medknow Publications, 2011)
Background : The choice of antimicrobial therapy for bloodstream infections is often empirical and based on the knowledge of local antimicrobial activity profiles of the most common bacteria causing such infections. Aims : The present study was aimed to investigate frequency of bacterial pathogens causing septicemia and their antimicrobial resistant pattern in hospital admitted patients. Settings and Design : It was a prospective study, conducted at Majeedia Hospital, Hamdard University, New Delhi, India. Material and Methods : We examined prospectively, 168 bacterial strains isolated from 186 clinically diagnosed septicemia cases admitted at a University Hospital in New Delhi, over a period of six months from July 2009 to December 2009. Antimicrobial susceptibility was performed according to Clinical and Laboratory Standards Institute (CLSI, USA) guidelines. Results : The most frequently identified Gram-positive bacteria were coagulase-negative staphylococci 63.5%, Staphylococcus aureus 23.1%, enterococci 5.8% and alpha-haemolytic streptococci 5.8%. The most frequently Gram-negative bacteria identified were Acinetobacter species 31%, Salmonella typhi 24.1%, Escherichia coli 23.3% and Pseudomonas aeruginosa 13.8%. Coagulase-negative staphylococci showed maximum resistance to cefaclor 57.1% and ampicillin 46.9%. Staphylococcus aureus showed maximum resistance to amoxicillin 100% and ampicillin 91.7%. Acinetobacter species showed maximum resistance to amoxicillin 89.7%, amoxiclav 87.1% and ampicillin 85.7%. Salmonella typhi, Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae showed maximum resistance to ampicillin, 46.4%, 92%, 93.8% and 100%, respectively. Conclusions : Gram-negative pathogens predominated in bloodstream infections. Resistance to most of the antimicrobial agents for a number of pathogens implicated in bloodstream infections, especially in Gram-negative bacteria, has reached worrisome levels and continues to increase.